1995
DOI: 10.1002/ijc.2910620107
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent amplification of cyclin E and CDK2 genes in colorectal carcinomas

Abstract: The genetic changes of cyclin A, DI, E and CDK2 were examined in human colorectal carcinomas by Southern-blot analysis. Gene amplification of cyclin E was detected in 5 of 53 (9.4%) primary colorectal carcinoma tissues. Interestingly, in 3 of 5 tumors showing cyclin E gene amplification, the CDK2 gene was amplified simultaneously with rearrangements. No obvious correlation was detected between gene amplification and clinicopathological features of colorectal carcinomas. Out of 7 colon carcinoma cell lines, 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
1
3

Year Published

1997
1997
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 12 publications
3
73
1
3
Order By: Relevance
“…Cyclin E/Ha-ras transformed cells ful®l the classical criteria for malignant cells as they are able to grow and form colonies independent of a solid support and give rise to malignant tumours in syngeneic animals. This oncogenic activity of cyclin E is most interesting in the light of recent reports that implicate the deregulation of cyclin E in human cancer particularly breast carcinoma (Keyomarsi et al, 1995;Kitahara et al, 1995) and strongly suggest a direct role of aberrant cyclin E expression in the formation of a number of human malignancies that bear ampli®ed cyclin E genes. With this activity of cyclin E and recent ®ndings that ascribe a similar oncogenic potential to CDK4 (Haas et al, 1997) and CDC25 (Galaktionov et al, 1995) as well as the similar already known activity of D-type cyclins strongly suggest that all genes encoding positive G1 cell cycle regulators are in general protooncogenes and that their deregulated expression leads to a loss of growth control that is incremental in the process of malignant transformation.…”
Section: Discussionmentioning
confidence: 82%
“…Cyclin E/Ha-ras transformed cells ful®l the classical criteria for malignant cells as they are able to grow and form colonies independent of a solid support and give rise to malignant tumours in syngeneic animals. This oncogenic activity of cyclin E is most interesting in the light of recent reports that implicate the deregulation of cyclin E in human cancer particularly breast carcinoma (Keyomarsi et al, 1995;Kitahara et al, 1995) and strongly suggest a direct role of aberrant cyclin E expression in the formation of a number of human malignancies that bear ampli®ed cyclin E genes. With this activity of cyclin E and recent ®ndings that ascribe a similar oncogenic potential to CDK4 (Haas et al, 1997) and CDC25 (Galaktionov et al, 1995) as well as the similar already known activity of D-type cyclins strongly suggest that all genes encoding positive G1 cell cycle regulators are in general protooncogenes and that their deregulated expression leads to a loss of growth control that is incremental in the process of malignant transformation.…”
Section: Discussionmentioning
confidence: 82%
“…43 Although amplification and overexpression of cyclin E have been shown in several human solid tumors, 43,44 little is known about the involvement of cyclin E in HCC. In the present study, we found increased levels of cyclin E protein and its kinase activity in moderately and poorly differentiated HCC (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…26 It is also well known that dysregulation of serine/threonine kinases may lead to uncontrolled cell proliferation and hence to cancer. For example, amplification of serine/threonine kinase genes such as CDK2 at 12q13, CDK4 at 12q14, PS6K at 17q23, and STK15 at 20q13 were observed in tumors of the ovary, 27 breast, 28,29 colon, 30 brain, 31,32 and cervix. 33 The strong association of TRIO amplification with high grade, advanced stage, and tumor cell proliferation suggests TRIO as appropriate oncogene candidate when amplified and overexpressed in bladder tumors.…”
Section: Discussionmentioning
confidence: 99%